Analisis Komoditas Basis Perekonomian Wilayah di Bagian Wilayah Kota (BWK) IV Kawasan Abeli Kota Kendari - Ido, Irfan (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2011)
The purpose of this study was: (1) know the commodity base in BWK IV Abeli Regions, (2) knew of the existence of commodity base in sub-district in Region IV Abeli BWK. The location of this research at Area BWK IV Abeli Region include sub-Anggoeya, Matabubu, Puday, Lapulu, Poasia, Talia, Nambo Bungkotoko, Abeli, Petoaha, Anggolomelai, Continental Nirae, Tobimeita, Sambuli, and Tondonggeu. When implementing the research on Agustus months to November 2009. Metode research analysis using the approach method and Richardson Gleason namely, methods of analysis Location Quotient (LQ). The conclusion of this research is: (1) the basis of these commodities in the agricultural sector BWK IV Abeli Region in Kendari is commodity cashew, coconut, cocoa, seaweed, beef, and chicken, spread on the sub-district. These commodities have value outside the region exports to the BWK IV Abeli Region both in scale and local trade, regional trade, (2) Areas of potential commodity development bases Cashew in villages Tondonggeu, Bungkutoko, Pudai, Continental Nirae, Sambuli, Anggoeya, Nambo, Poasia, Talia, and Abeli; Potential commodity development bases of Coconut in the village In Anggalomelai, Tobimeita, Matabubu, Bungkutoko, Abeli, Talia , Lapulu, Poasia, and Anggoeya; Potential commodity development cocoa in the village Nambo, Petoaha, Pudai, Tondonggeu, Poasia, Benua Nirae, and Sambuli; Potential of commodity development bases Seaweed in the village Sambuli, Tondonggeu, Bungkutoko; The potential development of commodity base Cow in the village Anggalomelai, Anggoeya, Abeli, Petoaha, Matabubu, and Benua Nirae; Potential commodity development bases Broiler in the village Pudai, Lapulu, Petoaha, Bungkutoko, Talia, Anggalomelai, Abeli, Tondonggeu, and Poasia.